2021
DOI: 10.3389/fpsyg.2021.691752
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Age-Prospective Memory Paradox Using Laboratory and Ecological Tasks

Abstract: Prospective memory (PM) is the ability to perform a planned action at a future time. Older adults have shown moderate declines in PM, which are thought to be driven by age-related changes in the prefrontal cortex. However, an age-PM paradox is often reported, whereby deficits are evident in laboratory-based PM tasks, but not naturalistic PM tasks. The key aims of this study were to: (1) examine the age-PM paradox using the same sample across laboratory and ecological settings; and (2) determine whether self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…They may also have experienced anxiety related to the novelty and the technological aspect of our laboratory PM task, which may have negatively influenced their results. These results are consistent with findings in other studies that showed that older individuals obtained lower results than younger ones on laboratory-type PM tasks (Haines et al, 2020; Koo et al, 2021). It would therefore be relevant to adapt research on PM with this population by substituting the TEMP by a similar but noncomputer-dependent task.…”
Section: Discussionsupporting
confidence: 93%
“…They may also have experienced anxiety related to the novelty and the technological aspect of our laboratory PM task, which may have negatively influenced their results. These results are consistent with findings in other studies that showed that older individuals obtained lower results than younger ones on laboratory-type PM tasks (Haines et al, 2020; Koo et al, 2021). It would therefore be relevant to adapt research on PM with this population by substituting the TEMP by a similar but noncomputer-dependent task.…”
Section: Discussionsupporting
confidence: 93%
“…(4) Multiple regression analyses identified age, gender and general intelligence as predictors of EPELI performance. Age-related impairments in PM have been observed especially in conventional PM tasks, but also in ecologically valid contexts [60], concurring with the present findings. Gender effects on PM have not received much attention, but the present gender difference favoring women is in line with other studies that have found gender effects [61].…”
Section: Discussionsupporting
confidence: 92%
“…Another important parameter affecting age differences is the source of PM task generation: participants performed better with self-generated intentions rather than experimenter-generated actions to perform. As a result of these findings, now, the so-called age PM paradox is no longer popular and research has shifted its focus toward cognitive factors more likely to explain individual differences in PM, such as executive functions, retrospective memory or IQ ( Hainselin et al, 2011 ; Azzopardi et al, 2015 ; Koo et al, 2021 ). Research has also focused on the ecological validity of PM tasks in assessing these factors involved in PM as well as their relationship with self-report measures ( Hainselin et al, 2021 ; Sugden et al, 2021a ).…”
Section: Conceptual Implicationsmentioning
confidence: 99%